International Students in the Crosshairs - Welch, Anthony (International Higher Education, 2024)
<h3 id="current-proposals-to-cap-international-enrollments-and-restrict-in-country-holders-of-visitor-and-graduate-visas-from-applying-for-student-visas-could-threaten-the-vitality-of-the-australian-higher-education-system-eroding-regional-relations-and-leading-to-major-financial-and-job-losses-the-proposed-establishment-of-the-australian-tertiary-education-commission-includes-expanding-the-level-of-ministerial-intervention-and-threatens-the-long-established-tradition-of-institutional-autonomy-including-in-relation-to-international-student-strategy" data-pm-slice="1 1 []">Current proposals to cap international enrollments and restrict in-country holders of visitor and graduate visas from applying for student visas could threaten the vitality of the Australian higher education system, eroding regional relations, and leading to major financial and job losses. The proposed establishment of the Australian Tertiary Education Commission includes expanding the level of ministerial intervention, and threatens the long-established tradition of institutional autonomy, including in relation to international student strategy.